A Dynamic Hajj Fiqh for Elderly: A Study of Indonesian Pilgrims - Badrah Uyuni; Mohammad Adnan (Research Synergy Foundation, 2024)
Hajj, one of the pillars of Islam, requires physical and mental capability, making it more suitable for healthy individuals. Recognizing the strong desire of older Muslims to perform Hajj, several countries have implemented